Microcomputers and static equilibrium - Reyes, Salvador F. (Philippine Engineering Journal)
This paper attempts to illustrate how traditional problem solving techniques in engineering statics might have to be modified or even supplanted by approaches which, though less than optimal for manual calculations, are actually the most suitable for microcomputers.